Antibacterial Activities of Garad (Acacia nilotica L.) Plant - Mohammed, Thowiba Mohamed Eltayeb; Abdel -Rahim Mohamed, Awad Mohamed (Gezira Journal of Engineering and Applied Sciences; Vol 12 No 1 (2017), 2017)
Garad is reported to has some antimicrobial activity. The aim of the present study is to investigate the antibacterial activities of the plant. The cup plate Inhibition zone method was used for some solvents tested. The results showed that the Garad pods extract was more effective against E. coli and S. paratyphi . However, the pods, bark and leaves extracts were highly effective against Staphylococcus sp. The solvent tests showed that the methanolic leaves extracts were effective against Staphylococcus sp. The ethanolic bark, seeds and pods extracts of Garad were effective against E. coli and S. paratyphi . All the petroleum ether and hexane extracts of the plant parts were not effective against all the tested bacteria.